Pengaruh Earning Per Share, Struktur Modal, Suku Bunga, dan Inflasi Terhadap Harga Saham pada Perusahaan Consumer Goods yang Terdaftar di BEI Tahun 2017-2019 - Ike Rukmana Sari; Patricia Patricia; Silvia Silvia (Universitas Batanghari Jambi, 2021)
The research we conducted was to determine the effect, analyze, and also get an understanding of whether Earning Per Share, Capital Structure (DER), Interest Rates, and Inflation simultaneously or partially affect Share Prices inCompanies Consumer Goods Listed on the IDX in 2017-2019. The population in this study were 50 companies and there were 60 companies that met the criteria as a sample with a purposive sampling technique. Multiple regression analysis and classical assumption test are the methods researchers use in this research. The results of the F test in this research show that simultaneously Earning Per Share, Capital Structure (DER), Interest Rates, and Inflation have an effect on share prices inCompanies Consumer Goods Listed on the IDX in 2017-2019. In the t test results, the variable Earning Per Share has an influence on the share price ofcompanies consumer goods listed on the IDX in 2017-2019, Capital Structure (DER) has an influence on the share price ofcompanies consumer goods listed on the IDX in 2017-2019, Interest Rates has no influence on the share price ofcompanies consumer goods listed on the IDX in 2017-2019, inflation has no effect on the share price ofcompanies consumer goods listed on the IDX in 2017-2019.